2022
DOI: 10.1021/acsomega.1c05089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intake Components and Stratification on the Particle and Gaseous Emissions of a Diesel Engine

Abstract: It is of great significance to improve the performance of diesel engines by adjusting the intake components and their distribution. In this work, various proportions of exhaust gas recirculation (EGR) gas and oxygen (O 2 ) have been introduced to the intake charge of a diesel engine and the effects of different intake components and stratification conditions on pollutant emissions, especially for particles, have been explored. The results show that the introduction of O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Cheng et al 26 studied the effect law of EGR on the performance of low-load diesel engine by bench test and found that as the EGR rate increases, the maximum in-cylinder burst pressure and heat release rate decrease and the average in-cylinder temperature decreases; when the EGR rate is low, the smoke increases with the increase of EGR rate, while with the further increase of the EGR rate, the smoke emission decreases and the CO and HC emissions increase rapidly. Zhang et al 27 designed a system in which the EGR gas component enters the cylinder simultaneously with oxygen, and the incoming oxygen with EGR can reduce both NO x and carbon soot emissions from diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al 26 studied the effect law of EGR on the performance of low-load diesel engine by bench test and found that as the EGR rate increases, the maximum in-cylinder burst pressure and heat release rate decrease and the average in-cylinder temperature decreases; when the EGR rate is low, the smoke increases with the increase of EGR rate, while with the further increase of the EGR rate, the smoke emission decreases and the CO and HC emissions increase rapidly. Zhang et al 27 designed a system in which the EGR gas component enters the cylinder simultaneously with oxygen, and the incoming oxygen with EGR can reduce both NO x and carbon soot emissions from diesel engines.…”
Section: Introductionmentioning
confidence: 99%